The idea of ​​justice from the recognition of the other: A contrast between the communitarianism of Luis Villoro and the contemporary Marxisms of Axel Honneth, Nancy Fraser and Michael Löwy - Valerio Mirada, David (2025)
The idea of justice from the recognition of the other in Luis Villoro’s communitarianism and contemporary Marxism’s sustain the possibility of collective projects, however, both proposals also preserve differences. On the other hand, in the face of the individualistic selfishness promoted by neoliberalism, it is prudent to analyze other alternatives to it.